Morphometric, histometric and histomorphological investigation of the effects of different ratios safflower (chartamus tinctorius l.) oil supplements on glandula uropygialis in japanese quails (coturnix coturnix japonica) - İsmail Demircioğlu; Bestami Yılmaz; Kürşat Filikçi; Gülşah Güngören; Faruk Bozkaya (Eurasian Journal of Veterinary Sciences)
Aim: The purpose of this studywas to investigate the effect of safflower oil added to the diet of Japanese quails (Coturnix coturnix japonica) on the morphometric, histometric and histomorphological featuresof glandula uropygialis. Materials and Methods: Daily rations of 40 Japanese quail were prepared supplementing with different levels of safflower oil. The quails were allocated to 4 experimental groups each consisting of 10 individuals (5 male and 5 female). All groups were fed with isoenergic ration containing 21% crude protein and 3100 kCal metabolic energy during six weeks. The control group consumed the basic ration (0% safflower oil) while experimental groups were fed with rations containing three different levels (0.1%, 0.2% and 0.3%) of safflower. Quails were slaughtered on 42nd day of the experiment and their glandula uropygialis were separated from the body to make morphometric measurements. Routine tissue processing was performed for histometric examination, then the tissues were stained with Haematoxylin-Eosin and Sudan Black. Results: The results indicated that safflower oil supplementatio had a significant effect on papillary length, left lobe length, glandular weight, relative glandular weight, glycogen region thickness(p<0.05) and right lobe length with (p<0.01). Significant differences were also observed between males and females in papillary length, wall thickness of glandular fat region (p<0.05) and live weight (p<0.001). Conclusion: As a result we suggested that safflower oil which is effective on lipid metabolism had significant impacts on the morphometric parameters of glandula uropygialis in Japanese quails. Further studies are necessary in order to assess the long term effect of safflower supplementation on the morphometry of glandula uropygialis in Japanese quails.